Study on the adsorption properties of organically modified diatomite for methylene blue - Ziying Bu; Ying Fang; Hanjie Chen; Mei Zhang; Fulong Wang (Scientific Reports)
Abstract Methylene blue (MB) dye is highly stable and non-degradable under natural conditions, posing significant threats to both ecosystems and human health. Conventional adsorbents, such as metal oxides, zeolites, bioadsorbents, and activated carbon, suffer from limited porosity, which restricts their adsorption efficiency. Moreover, their high cost results in low economic viability. In this study, a novel eco-friendly crosslinked diatomite–chitosan/calcium alginate (DM-CS@CA) composite powder was synthesized using diatomite (DM), chitosan (CS), and sodium alginate (SA) as raw materials. The composite was prepared without the use of any chemical crosslinking agents, employing encapsulation techniques and drying processes. The adsorbent was characterized and analyzed using a range of techniques, including Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and atomic force microscopy (AFM). Analysis of the experimental data revealed that the adsorption isotherm fits well with the Langmuir model, and the adsorption kinetics are consistent with the pseudo-second-order model. Under optimal conditions of pH 8, temperature 25 °C, and an adsorbent dosage of 1 g/L, the maximum adsorption capacity reached 549.74 mg/g.